The data journalism handbook towards a critical data practice - Bounegru, Liliana 198X-; Gray, Jonathan 1975- (Amsterdam University Press, 2021)
The Data Journalism Handbook: Towards a Critical Data Practice provides a rich and panoramic introduction to data journalism, combining both critical reflection and practical insight. It offers a diverse collection of perspectives on how data journalism is done around the world and the broader consequences of datafication in the news, serving as both a textbook and a sourcebook for this emerging field. With more than 50 chapters from leading researchers and practitioners of data journalism, it explores the work needed to render technologies and data productive for journalistic purposes. It also gives a 'behind the scenes' look at the social lives of datasets, data infrastructures, and data stories in newsrooms, media organizations, startups, civil society organizations and beyond. The book includes sections on 'doing issues with data', 'assembling data', 'working with data', 'experiencing data', 'investigating data, platforms and algorithms', 'organizing data journalism', 'learning data journalism together' and 'situating data journalism'
Erscheint als Open Access bei De Gruyter
Keywords: Data Mining; Journalismus; Aufsatzsammlung